Tingkat Kesiapsiagaan Siswa dalam Menghadapi Bencana Banjir di SMA Negeri 1 Perhentian Raja Kabupaten Kampar Provinsi Riau - Ilma Zulfina; Dedi Hermon (Jurnal Penelitian Pendidikan IPA, 2025)
Floods are one of the natural disasters that often occur in Indonesia, including in Riau Province. Kampar Regency, especially the Perhentian Raja area, is one of the areas prone to flood disasters. caused by the morphological and physical conditions of the area which is dominated by lowlands and surrounded by large rivers such as the Kampar and Siak rivers and other rivers in Kampar Regency. This research aims to 1). Knowing the impact of the flood disaster at SMA Negeri 1 Perhentian Raja, Kampar Regency, Riau Province. 2). Analyzing the level of preparedness of students facing flood disasters at SMA Negeri 1 Perhetian Raja, Kampar Regency, Riau Province, 3). Formulating a strategy for developing students' preparedness for flood disasters at SMA Negeri 1 Perhentian Raja. This research was conducted using mixed research (Mix Methods) with quantitative and qualitative approaches, and using the AHP method (analytical Hierarchy Proces) to formulate strategies for developing student preparedness. Data collection using interviews, questionnaires, FGD (Focus group discussion), and analysis) . The research results show that 1). The impact of the flood disaster at SMA Negeri 1stop Raja showed a light impact on the physical and environmental aspects of the school. 2). The level of preparedness of students in facing flood disasters at SMA Negeri 1 Perhentian Raja was obtained using 5 parameters. The total number of parameters entered the average index of 86.4% in the very prepared category. 3). The strategy for developing students' preparedness to face flood disasters at SMA Negeri 1 Perhentian Raja uses the method Analytical hierarchy proces got 9 alternatives. This alternative was formulated to reduce the risk of flood disasters at SMA Negeri 1 Perhentian Raja.